Removing user fees : learning from international experience to support the process - McPake, Barbara [et al] (2011)
Article advocates the removal of user fees in the health sector in order to improve service coverage and access especially among the poorest socio-economic groups. Proposes six steps for a successful policy change to maximise benefits and avoid potential pitfalls.